PENYELESAIAN PERJANJIAN KREDIT BANK SEBAGAI AKIBATFORCE MAJEURE KARENA GEMPA DI YOGYAKARTA - Lathifah Hanim; MS. Noorman (UNISSULA, 2016)
Pursuant to Article 1338 of the Civil Code, any agreement must be subject to the principle of good faith (bona fide / good faith) in its implementation because of its binding nature as a law. Exceptions to those provisions are found in the provisions governing the conditions of force majeure in Article 1244 and Article 1245 Civil Code. The legal system of the Civil Code does not introduce the principle of poached sic stantibus in the realm of covenant law, but rather put forward the aspects of force majeure. In banking practice in Indonesia, generally the bank credit agreement used is a standard agreement or a standard agreement in which clauses have been prepared previously by the bank. Accordingly, the customer as a debtor candidate has only the choice between accepting the entire contents of the agreement clauses or not willing to accept the clauses either partially or wholly resulting in the customer not receiving the credit. The formulation of the problem is how the bank's efforts in the settlement of the credit agreement of the bank as a result of force majeure, due to the earthquake in Yogyakarta. This research uses the concept of doctrinal and non doctrinal law. Non-doctrinal legal research, the approach is 2 (two) that is qualitative and quantitative. This research uses qualitative research. The result of the research is the effort of bank in the settlement of bank credit agreement as a result of force majeure, because the earthquake in Yogyakarta is done by recheduling (Rescheduling payment), reconditioning (Partial / total terms changes from credit), restructuring (Re-arrangement of credit terms), Execution of guarantee through auction and PBI Number 8/10 / PBI / 2006, PBI Number 8/15 / PBI / 2006, PBI. 11/27 / PBI / 2009.